The anti-oxidative and hemostasis-related multifunctionality of L-chicoric acid, the main component of dandelion: An in vitro study of its cellular safety, antioxidant and anti-platelet properties, and effect on coagulation. (November 2019) - Lis, Bernadetta; Jedrejek, Dariusz; Moldoch, Jaroslaw; Stochmal, Anna; Olas, Beata
Graphical abstract: Highlights: Chicoric acid has different biological properties without cytotoxicity. Dandelion leaves are a rich source of chicoric acid. 50% fraction from dandelion leaves had the best anti-platelet activity. Chicoric acid did not change coagulation times of human plasma. Abstract: All dandelion ( Taraxacum officinale ) organs, i.e. the roots, leaves and flowers, are rich in L-chicoric acid, and nowadays are commonly included in dietary products and pharmaceutical preparations. However, little is known of the effects of dandelion leaves and petals, or L-chicoric acid itself, on the biological activity hemostasis elements such as blood platelets and plasma. Therefore, the aim of the present study was to examine the effect of chicoric acid extracted from dandelion on the biological properties of human plasma and blood platelets in vitro . Briefly, the study evaluated the effects of four phenolic fractions, obtained from leaves (fraction A and B) and petals (fraction C and D), with different concentrations of chicoric acid, as well as L-chicoric acid isolated from dandelion leaves, on biomarkers of oxidative stress, parameters of coagulation and blood platelet activation. Chicoric acid offers novel antioxidant and anti-adhesive potential without cytotoxicity.